(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
Learning foreign languages is important in modern society. Globalization processes, cultural exchanges and economic cooperation increase the need-to-know foreign languages. Today, there are various methods of learning foreign languages, each of them has its own advantages and disadvantages. This article provides detailed information about modern methods of learning foreign languages, their effectiveness and practice.